2017
DOI: 10.5604/01.3001.0009.5858
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection among patients after colorectal cancer surgery

Abstract: Wstęp: Zakażenie miejsca operowanego występuje u 2,5-22,3% operowanych chorych. Jest ono wykładnikiem jakości leczenia na oddziałach zabiegowych i ma duży wpływ na jego koszt. Materiał i metodyka: Analizie poddano chorych, u których w obserwacji 30-dniowej wystąpiło zakażenie miejsca operowanego. Grupę wyjściową stanowiło 1581 chorych z rozpoznaniem raka jelita grubego poddanych zabiegowi operacyjnemu w jednym ośrodku. Kryteriami wyłączającymi z badania były: brak wiarygodnej dokumentacji leczenia (szpitalnego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
3
11
0
3
Order By: Relevance
“…The higher risk of acquiring SSI among patients with malignant diseases compared to patients with benign diseases is reasonable since malignancy is associated with weak immune system and vulnerability to various infections, and it is consistent with studies reported that SSI was observed in 30-60% of patients after colorec tal cancer surgeries (5,(14)(15). The lack of association between SSI and timing of SAP is similar to another retrograde cohort study (28).…”
Section: Discussionsupporting
confidence: 88%
“…The higher risk of acquiring SSI among patients with malignant diseases compared to patients with benign diseases is reasonable since malignancy is associated with weak immune system and vulnerability to various infections, and it is consistent with studies reported that SSI was observed in 30-60% of patients after colorec tal cancer surgeries (5,(14)(15). The lack of association between SSI and timing of SAP is similar to another retrograde cohort study (28).…”
Section: Discussionsupporting
confidence: 88%
“…Although there are global variations around the definition of an SSI, the European Commission classified SSIs into superficial incisional surgical site infection, deep incisional surgical site infection, or surgical site infection -organ/space, and the diagnostic criteria include the presence of one of the signs of infection (tenderness, swelling, reddening, and elevated skin temperature), purulent discharge from the incision site, and positive result of microbiological examination of material collected or after the surgical opening of the incision site [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo retrospectivo conduzido com 1.581 pacientes submetidos à cirurgia colorretal para ressecção de câncer, no período de 1994 a 2016, cujo objetivo foi identificar os fatores de risco e o impacto de ISC, a taxa de ISC foi de 12,52% (n=198) (BANASZKIEWICZ et al, 2017).…”
Section: Indicadores De Incidência De Infecção Do Sítio Cirúrgico (Isc)unclassified
“…No estudo de Banaszkiewicz et al (2017) com pacientes submetidos a cirurgia colorretal para ressecção de câncer, dos 198 casos de infecção (taxa de ISC de 12,52%), 102 foram de ISC incisional-superficial (6,45%), 34 de ISC incisionalprofunda (2,15%), e 62 de órgão/cavidade (3,92%).…”
Section: Indicadores De Incidência De Infecção Do Sítio Cirúrgico (Isc)unclassified
See 1 more Smart Citation